2022
DOI: 10.3390/healthcare10061024
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low Frequency Sound on Heart Rate Variability and Subjective Perception: A Randomized Crossover Study

Abstract: Background: Vibroacoustic therapy (VAT) uses low-frequency sound, often combined with listening to music, for therapeutic purposes. However, the impact of low-frequency vibration (LFV) on physiological functions and subjective perception is relatively unknown. Methods: We conducted a randomized cross-over study with the aim of comparing the effect of constant LFV of 40 Hz, its amplitude modulation, and the placebo condition on heart rate variability (HRV), stress perception (measured by visual analogue scales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
(41 reference statements)
0
6
1
Order By: Relevance
“…Nevertheless, there was a trend toward better negative affect recovery in the bird and water sounds compared to the control sound. Also in literature, nuances exist within the subjective reports: bird song improved positive but not negative mood (Benfield et al, 2014), while river sounds in another study stimulated recovery in self-reported stress and HRV but not in emotions (Vilímek et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there was a trend toward better negative affect recovery in the bird and water sounds compared to the control sound. Also in literature, nuances exist within the subjective reports: bird song improved positive but not negative mood (Benfield et al, 2014), while river sounds in another study stimulated recovery in self-reported stress and HRV but not in emotions (Vilímek et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Amplitude modulations were first studied by Wigram (1997) and further explored in various experiments by additional researchers (Vilímek et al, 2019(Vilímek et al, , 2022; including authors of this study). Sequenced modulations of LFS make it possible to minimize some secondary complications in frequent vibroacoustic sessions described as overstimulation (Wigram, 1996).…”
Section: Introductionmentioning
confidence: 86%
“…Although university counseling centers offer essential support services, many students would benefit from developing further preventive non-pharmacological strategies, especially those that could offer immediate relief of stress symptoms and help cope with situational demands, thereby contributing to health promotion in educational institutions. Based on results of empirical observations ( Skille, 1989 ), as well as pilot studies ( Delmastro et al, 2018 ; Vilímek et al, 2022 ), a potential method for coping with acute stress response may be found in vibroacoustic therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the field remains unestablished. Preliminary research infers the intervention can relieve stress [28] though assessment of this is scarce [29][30][31][32]. To the authors knowledge, four studies to date specifically compare the effect of vibroacoustic interventions on stress using biosignal measurements.…”
Section: State Of the Artmentioning
confidence: 99%